Pengaruh Financial Attitude dan Kontrol Diri Terhadap Pengelolaan Keuangan Mahasiswa S1 Pendidikan Ekonomi Universitas Negeri Malang Angkatan 2018 - Na’imatul Jannah; Syahrul munir (Jurnal Pendidikan Ekonomi, 2021)
This research aims to determine the effect of financial attitudes and self-control on financial management of undergraduate students of Economics Education, Universitas Negeri Malang  Class 2018. The type of research used is quantitative explanatory. The sample used was 100 of 133 undergraduate students of Economics Education, Universitas Negeri Malang obtained through the slovin formula. The data collection technique used is a questionnaire. The data analysis technique used is the classical assumption test, multiple linear analysis and hypothesis testing (t test and F test) with the help of SPSS 25.00 for windows. Based on the analysis of the results as follows: 1) financial attitudes have a partial effect on the financial management of S1 students of Economics Education, Universitas Negeri Malang  , Class of 2018, 2) self-control partially affects the financial management of students of Economics, Universitas Negeri Malang, Class of 2018, 3) Financial attitudes and self-control simultaneously affect the financial management of undergraduate students of Economics Education, Universitas Negeri Malang Class of 2018